A superhydrophobic unsaturated transition metal chalcogenide, its synthesis method and application
By synthesizing superhydrophobic unsaturated transition metal chalcogenides with uniform pore structure and surface defect sites under strongly acidic conditions, the problem of efficiency reduction of chalcogenides under water vapor was solved, and the self-regulation of efficient adsorption and catalytic performance was achieved, which is suitable for smelting flue gas treatment and carbon dioxide reduction.
Patent Information
- Application Number
- CN202310750573.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2025-12-02
- Estimated Expiration
- 2043-06-25
AI Technical Summary
Existing methods for chalcogenides exhibit reduced efficiency in the presence of water vapor, and are complex and costly, making it difficult to achieve self-regulation of the hydrophilicity and hydrophobicity of chalcogenides.
By reacting chalcogenides with transition metal cations under strongly acidic conditions, superhydrophobic unsaturated transition metal chalcogenides with uniform pore structure and surface defect sites are formed. The hydrophobicity of the unsaturated sulfur sites and the pore structure are used to improve adsorption and catalytic performance.
It achieves high adsorption and catalytic performance under high humidity conditions, reduces preparation costs, broadens the application range, and is suitable for smelting flue gas treatment and carbon dioxide reduction, etc.
Smart Images

Figure CN117023519B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental pollution prevention and control and clean energy utilization technology, and relates to a chalcogenide compound, its synthesis method and application, specifically a superhydrophobic unsaturated transition metal chalcogenide compound, its synthesis method and application. Background Technology
[0002] Chalcogenides, due to their unique properties, have broad application prospects in environmental pollution control and clean energy utilization. For example, chalcogenides are rich in sulfur sites with strong affinity for heavy metals, which can solidify heavy metals such as mercury, arsenic, cadmium, and lead into MS / M-Se form (where M is the heavy metal ion). Heavy metal compounds in MS / M-Se form are extremely stable and can be directly landfilled and stored in the earth's crust, to be used as mineral raw materials for the industrial production of the corresponding heavy metals when needed. Furthermore, most chalcogenides are semiconductors and can be used as thermal / photocatalysts for energy conversion and clean utilization. A typical example is using MoS2 as a catalyst to achieve electrocatalytic CO2 reduction and synthesize hydrocarbon fuels. This method can effectively convert intermittent clean energy (such as wind, solar, and tidal energy) into chemical energy for storage, alleviating the problems caused by the surge in global energy demand and the depletion of fossil fuels.
[0003] Although chalcogenides have a wide range of applications, their efficiency can be significantly suppressed in some applications due to the presence of water vapor or liquid water. For example, Chinese patent CN115888625A discloses a method for enhancing the mercury removal performance of metal sulfides, which prepares metal sulfides by mixing and reacting a soluble metal salt solution with a sulfur-containing ion solution. However, because this metal sulfide introduces sulfide anions instead of sulfides, its mercury removal performance is affected by sulfide. 0 The removal rate and mercury removal performance in atmospheres with high water content are insufficient, mainly because most chalcogenides are hydrophilic. This leads to a large number of water molecules adsorbing onto the surface of chalcogenides, competing with other components for active sites, resulting in a significant decrease in conversion efficiency. For example, in metallurgical flue gas, the water vapor content can reach over 10%. During the removal of heavy metal pollutants from metallurgical flue gas using chalcogenides, water molecules often preferentially adsorb onto the surface of chalcogenides before heavy metals, causing deactivation of the metal sulfide compounds. In addition, metallurgical flue gas often contains a large amount of smelting slag. If hydrophobic materials are used, the smelting slag on the surface of the adsorbent can be washed away by spraying water to maintain the heavy metal removal effect of the adsorbent. However, for hydrophilic materials, the heavy metal adsorption effect will not only not improve after water washing, but may even decrease further. For another example, in the catalytic reduction of CO2, if excessive water molecules adsorb onto the surface of chalcogenides, water will be reduced before CO2, reducing the CO2 reduction efficiency.
[0004] In summary, developing hydrophobic chalcogenide materials is of great significance for broadening their application range and reducing their application costs. However, most current methods for improving the water resistance of chalcogenides involve loading the chalcogenides onto the surface of hydrophobic materials or encapsulating them within hydrophobic frameworks. Typical supports include hydrophobic activated carbon, and typical hydrophobic frameworks include metal-organic frameworks such as MCM-48 / MCM-41. These methods involve complex processes and are costly. Developing a universally applicable method to achieve self-regulation of the hydrophilicity and hydrophobicity of chalcogenides remains one of the main challenges facing the industrial application of chalcogenides. Summary of the Invention
[0005] To overcome the shortcomings of the prior art, the first objective of this invention is to provide a superhydrophobic unsaturated transition metal chalcogenide, which is composed of unsaturated chalcogenide anions and transition metal cations. It possesses a uniform pore structure and numerous surface defect sites, exhibiting good adsorption performance. Furthermore, its rich content of unsaturated sulfur (selenium) sites not only makes it superhydrophobic but also enhances its selective adsorption performance for nonpolar atoms and molecules. Therefore, it can be used for the removal of heavy metals or oxides from flue gas, and is particularly suitable for high-humidity flue gas treatment. Simultaneously, this transition chalcogenide has numerous catalytically active sites, exhibiting good catalytic activity. Moreover, its pore structure and highly hydrophobic surface facilitate the adsorption and capture of oxidizing gases such as carbon dioxide, significantly improving its catalytic conversion efficiency.
[0006] The second objective of this invention is to provide a method for synthesizing superhydrophobic unsaturated transition metal chalcogenides. This method is simple to operate, has low raw material costs, and has high versatility and industrial application potential. It can synthesize superhydrophobic transition metal chalcogenides without introducing any other hydrophobic carriers or frameworks.
[0007] The third objective of this invention is to provide an application of a superhydrophobic unsaturated transition metal chalcogenide, which can be used as an adsorbent for elemental heavy metals and / or heavy metal oxides, suitable for treating smelting flue gas, especially high-humidity smelting flue gas, and can also be used as an electrocatalyst for the catalytic reduction of oxidizing gases, particularly suitable for the reduction and conversion of carbon dioxide into hydrocarbons.
[0008] To achieve the above-mentioned technical objectives, the present invention provides a method for synthesizing superhydrophobic unsaturated transition metal chalcogenides. The method involves heating chalcogenide powder to above the melting temperature to form molten chalcogenides, mixing the molten chalcogenides with a reducing agent to undergo a disproportionation reaction, and then adding a strongly acidic solution containing transition metal cations for aging to obtain the final product.
[0009] This invention involves heating and reductively disproportionating chemically inert chalcogenides to form long-chain chalcogen anions. Excess long-chain chalcogen anions are then reacted with transition metal cations under specific pH conditions to form a transition metal chalcogenide compound with a superhydrophobic surface, rich in a uniform porous structure and surface defect sites. This transition metal chalcogenide compound introduces abundant unsaturated sulfur (selenium) sites. These unsaturated sulfur (selenium) sites have very low adsorption energies for water molecules, or even cannot adsorb them, effectively repelling water molecules and creating a superhydrophobic surface. Furthermore, these unsaturated sulfur (selenium) sites further reduce the adsorption energy of nonpolar atoms / molecules, thereby improving the adsorption selectivity of the transition metal chalcogenide compound for nonpolar atoms / molecules. In addition, the synthesis of the transition metal chalcogenide compound under strongly acidic conditions can utilize hydrogen ions (H+)... + During the nucleation process of metal sulfides, it reacts with some sulfur ions (S). 2- The reaction occurs and volatilizes in the form of H2S, thereby constructing a uniform pore structure and a large number of surface defect sites in the transition metal chalcogenides. These pore structures and surface defect sites can endow the transition metal chalcogenides with good adsorption properties, while exposing more catalytic active sites.
[0010] Taking elemental sulfur or elemental selenium as an example, the mechanism of this invention is as follows: using powdered elemental sulfur or elemental selenium as raw materials, unsaturated long-chain chalcogenide anions are obtained through ring-opening and disproportionation reactions. Transition metal chalcogenides are then synthesized through the reaction of excess chalcogenide anions with transition metal cations. After ring-opening upon heating, powdered elemental sulfur or elemental selenium exists in the form of sulfur chains or selenium chains (i.e., forming molten chalcogenides). Upon addition of a reducing agent, it can be reduced to negatively valence sulfur chains or selenium chains. These sulfur chains and selenium chains react with transition metal cations to synthesize chalcogenides rich in unsaturated sulfur / selenium sites (i.e., chain-like sulfur or selenium sites). The reaction equation is as follows:
[0011] S x / Se x (Circular) → S x / Se x (Chain-like)
[0012] S x / Se x (Chain-like) + reducing agent → S x n- / S x n- (0 <n<2)
[0013] S x n- / S xn- +M 2+ →M-(S x n- / S x n- ) 2 / n ;
[0014] In the synthesis of the chalcogenides of this invention, the reaction occurs under strongly acidic conditions, and hydrogen ions (H+) react to form ions. + It can react with sulfur ions (S) during the nucleation of metal sulfides. 2- A reaction occurs during leaching of S. 2- Simultaneously, the product H2S partially volatilizes, thereby constructing a uniform porous structure and surface defect sites in the metal sulfide. The specific reaction equation is as follows (taking a divalent transition metal cation as an example, M...). 2+ ):
[0015] H + +MS→HS - +M 2+
[0016] H + +HS - →H2S(g)
[0017] As a preferred embodiment, the chalcogenides include elemental sulfur and / or elemental selenium. When using powdered elemental sulfur, it needs to be heated to above 120°C to reach a molten state; when using powdered elemental selenium, it needs to be heated to above 220°C to reach a molten state. The heating process can achieve ring-opening of chemically inert elemental sulfur or bond breaking of elemental selenium, thereby facilitating its disproportionation reaction in a reducing agent.
[0018] As a preferred embodiment, the transition metal cation is at least one selected from copper, zinc, cadmium, cobalt, iron, molybdenum, and nickel. The solution containing the transition metal cation in this invention is obtained by dissolving precursors of copper, zinc, cadmium, cobalt, iron, molybdenum, and nickel in water, such as sulfuric acid, chloride, nitric acid, or acetic acid salts.
[0019] As a preferred embodiment, the reducing agent is at least one selected from sodium hydroxide, sodium borohydride, sodium thiosulfate, potassium hydroxide, potassium borohydride, and transition metal potassium thiosulfate. In this invention, the reducing agent can reduce the sulfur or selenium chain after ring-opening or bond-breaking to a negatively valence state.
[0020] As a preferred embodiment, the molar ratio of the chalcogenide powder to the transition metal cation in the solution containing transition metal cations is 2–20:1. In this invention, it is necessary to ensure that the chalcogenide powder is in excess to ensure that the ratio of sulfur / selenium to transition metal ions in the generated transition metal chalcogenide compound is greater than 1:1, thereby ensuring the formation of unsaturated anion sites in the transition metal chalcogenide compound. More preferably, the molar ratio of the chalcogenide powder to the transition metal cation is 12–20:1.
[0021] As a preferred embodiment, the amount of reducing agent added is at least 1.5 times the mass of the chalcogenide powder. The amount of reducing agent used in this invention ensures sufficient reduction of the sulfur or selenium chains after ring-opening or bond breaking. More preferably, the amount of reducing agent added is at least 2 times the mass of the chalcogenide powder.
[0022] As a preferred embodiment, the pH of the strongly acidic solution containing transition metal cations is 0-2. In this invention, the pH is adjusted to ensure the solution system is in a strongly acidic environment, thus increasing the concentration of hydrogen ions (H+) in the strong acid. + It can react with sulfur ions (S) during the nucleation of transition metal sulfides. 2- A reaction occurs during leaching of S. 2- Simultaneously, some of the H2S product volatilizes, thereby constructing a uniform porous structure and surface defect sites within the transition metal sulfide. If the pH of the strongly acidic solution is greater than 2, the hydrophobic properties of the unsaturated transition metal chalcogenides will decrease.
[0023] As a preferred embodiment, the present invention uses substances such as perchloric acid, hydroiodic acid, sulfuric acid, hydrobromic acid, hydrochloric acid, nitric acid, iodic acid, oxalic acid, nitrite, acetic acid, citric acid, and hydrofluoric acid, which can release an appropriate amount of hydrogen ions in aqueous solution, to adjust the pH of the solution to 0-2.
[0024] As a preferred embodiment, the conditions for the disproportionation reaction are: a temperature of 20–220°C and a time of 10–120 min.
[0025] As a preferred embodiment, the aging process is carried out at room temperature and pressure for 2 to 24 hours.
[0026] This invention also provides a superhydrophobic unsaturated transition metal chalcogenide prepared by the above method. This superhydrophobic transition metal chalcogenide possesses a uniform pore structure and surface defect sites, exhibiting good adsorption performance. Furthermore, the introduction of unsaturated chalcogen anions provides abundant unsaturated sulfur (selenium) sites, not only making it superhydrophobic (water contact angle greater than 100°) but also improving its selective adsorption performance for nonpolar atoms and molecules. Simultaneously, this transition metal chalcogenide has a large number of catalytically active sites, exhibiting good catalytic activity. Moreover, its pore structure and highly hydrophobic surface facilitate the adsorption and capture of oxidizing gases, significantly improving its catalytic conversion efficiency.
[0027] The excellent water resistance of the transition metal chalcogenides in this invention is mainly based on the change in the number of unsaturated sulfur (selenium) sites on the surface of the transition metal chalcogenides. Density functional theory calculations show that as the number and abundance of unsaturated sites on the surface of the transition metal chalcogenides increase, the adsorption energy of water on the surface of the transition metal chalcogenides gradually decreases. When the coverage of unsaturated sulfur (selenium) sites is higher than 20%, the adsorption energy of water molecules changes from negative to positive, indicating that water molecules cannot adsorb onto the surface of the transition metal chalcogenides under this condition. This transforms the transition metal chalcogenides from hydrophilic materials to hydrophobic materials. (See [link to related documentation]). Figure 1 .
[0028] Furthermore, density functional theory calculations show that for molecules with weaker dipole moments than water (such as heavy metals and CO2), increasing the number of unsaturated sulfur (selenium) sites not only does not inhibit their adsorption but also further promotes it, widening the adsorption energy gap between the target atoms / molecules and water molecules. This is more conducive to the transformation of target atoms / molecules on the surface of transition metal chalcogenides, significantly improving their water resistance. See [link to relevant documentation]. Figure 2 (Taking mercury atoms as an example.)
[0029] As a preferred embodiment, the chalcogen elements in the superhydrophobic unsaturated transition chalcogenide compound do not exist entirely in their lowest valence form, and the prepared material is either crystalline or amorphous.
[0030] As a preferred embodiment, the content of unsaturated transition metal chalcogenides (i.e., -1 or 0 valence) in the superhydrophobic chalcogenide compound is not less than 20%.
[0031] This invention also provides an application of superhydrophobic unsaturated transition metal chalcogenides as adsorbents for heavy metals and / or heavy metal oxides, suitable for treating smelting flue gas, particularly high-humidity smelting flue gas. The efficiency of chalcogenides synthesized in high-humidity smelting flue gas treatment is reduced by no more than 5% compared to anhydrous conditions. Examples of heavy metals include mercury. Examples of heavy metal oxides include arsenic oxide.
[0032] This invention also provides an application of a superhydrophobic unsaturated transition metal chalcogenide as an electrocatalyst for the catalytic reduction of oxidizing gases, which is particularly suitable for the reduction and conversion of carbon dioxide into hydrocarbons.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] (1) The method of the present invention has a simple preparation process, and can achieve self-regulation of the hydrophilic and hydrophobic properties of transition metal chalcogenides without introducing any other compounds. Moreover, the preparation cost is low, and the synthesis process does not involve hydrothermal methods, titration methods, or other methods that are difficult to scale up production. It has the potential for industrial application.
[0035] (2) The method proposed in this invention has strong universality. Using this method, a variety of transition metal chalcogenides with hydrophobicity can be prepared.
[0036] (3) The water contact angle of the transition metal chalcogenides provided by the present invention is greater than 140°, and the synthesized materials have strong hydrophobic properties. Under the condition of 20% water content (higher than 99% of industrial application scenarios), 100% water resistance can be achieved.
[0037] (4) The transition metal chalcogenide provided by this invention has a uniform pore structure and surface defect sites, exhibiting good adsorption performance. Furthermore, the introduction of unsaturated chalcogenide anions and the abundance of unsaturated sulfur (selenium) sites not only make it superhydrophobic but also improve its selective adsorption performance for nonpolar atoms and molecules. Simultaneously, this transition metal chalcogenide has a large number of catalytically active sites, exhibiting good catalytic activity. Moreover, its pore structure and highly hydrophobic surface facilitate the adsorption and capture of oxidizing gases, greatly improving its catalytic conversion efficiency.
[0038] (5) The transition metal chalcogenides synthesized in this invention have broad application prospects. They can be used as adsorbents for elemental heavy metals and / or heavy metal oxides, suitable for smelting flue gas treatment, especially high-humidity smelting flue gas treatment. They can also be used as electrocatalysts for oxidizing gas catalytic reduction, particularly suitable for the reduction and conversion of carbon dioxide into hydrocarbons.
[0039] (6) The transition metal chalcogenides synthesized in this invention can be further loaded onto any support without losing their hydrophobicity and water resistance, thus further broadening the range of support options and application prospects. Attached Figure Description
[0040] Figure 1The graph shows the variation of adsorption energy of water molecules on cobalt sulfide with different coverage of unsaturated sulfur sites, where the coverage of unsaturated sulfur sites in Figures (a), (b), (c), and (d) is 0%, 10%, 30%, and 50%, respectively.
[0041] Figure 2 It consists of water molecules (H2O) and mercury atoms (Hg). 0 The graph shows the variation of adsorption energy on cobalt sulfide with different coverage of unsaturated transition metal sulfur sites on the surface. It can be seen from the graph that when the coverage of unsaturated transition metal sulfur sites on the surface is higher, the adsorption energy of water molecules is higher, indicating better hydrophobicity. At the same time, the adsorption energy of mercury atoms is lower, indicating better adsorption performance for mercury atoms. Detailed Implementation
[0042] The technical solution of the present invention will be further described below through specific embodiments. These embodiments are not intended to limit the scope of protection.
[0043] Example 1
[0044] (1) Take 0.2 mol of sulfur powder and heat it to a molten state in a drying oven at 200℃. Add 100 mL of 5 mol / L potassium borohydride solution to the molten sulfur. Stir at room temperature for 90 min. Then dissolve 0.01 mol of cadmium chloride in 100 mL of hydrochloric acid solution with pH 0.5 and pour it into the potassium borohydride solution of sulfur. Let the precipitate age for 24 h. Wash the synthesized sample 5 times with deionized water. After solid-liquid separation, place the sample in a drying oven and dry at 60℃ for 24 h. Pass it through a 100-mesh sieve to obtain superhydrophobic cadmium sulfide adsorbent. Use a water contact angle tester (OCA20, Germany) to test the hydrophobicity of the prepared cadmium sulfide. The water contact angle of cadmium sulfide was measured to be 140°, which belongs to superhydrophobic materials.
[0045] (2) Weigh 200 mg of adsorbent and place it in a cylindrical quartz glass fixed-bed reactor. Heat the standard As2O5 liquid to its boiling point to produce gaseous As2O3, using nitrogen gas at a flow rate of 1 L / min as the carrier gas. The initial As2O3 concentration is 50 ± 5 μg / m³. 3 The reaction temperature was 150℃, and the concentrations of As2O3 at the inlet and outlet were measured using an HG-AFS instrument. Under pure N2 and N2 + 20% H2O atmospheres, the removal rates of As2O3 were 100% and 100% after 3 hours, respectively.
[0046] Example 2
[0047] (1) Take 0.03 mol of sulfur powder and heat it to the molten state in an oil bath at 140℃. Add 100 mL of 0.5 mol / L sodium borohydride solution to the molten sulfur. Stir at room temperature for 120 min. Then pour 50 mL of cobalt nitrate solution with pH 1 (cobalt nitrate content is 0.01 mol) into the sulfur sodium borohydride solution. The resulting precipitate is aged for 12 h. Wash the synthesized sample 5 times with deionized water. After solid-liquid separation, place the sample in a drying oven and dry at 60℃ for 12 h. Pass it through a 100-mesh sieve to obtain hydrophobic cobalt sulfide adsorbent. Use a water contact angle tester (OCA20, Germany) to test the hydrophobicity of the prepared cobalt sulfide. The water contact angle of cobalt sulfide is measured to be 149°, which belongs to superhydrophobic material.
[0048] (2) Weigh 20 mg of adsorbent and place it in a cylindrical quartz glass fixed-bed reactor. Elemental mercury is generated through a mercury permeation tube, using nitrogen gas at a flow rate of 1 L / min as the carrier gas. The initial mercury concentration is 100 ± 1 μg / m³. 3 The reaction temperature was 100℃, and the concentration of elemental mercury at the inlet and outlet of the reactor was monitored using a VM3000 mercury analyzer. Simulated flue gas N2, N2 + 5% H2O, N2 + 10% H2O, and N2 + 20% H2O were added respectively. The Hg levels within 2 hours were monitored. 0 The adsorption efficiencies were 100%, 100%, 100%, and 100%, respectively.
[0049] Example 3
[0050] (1) Take 0.025 mol of selenium powder and heat it to a molten state in a drying oven at 240℃. Add 100 mL of 0.5 mol / L potassium hydroxide solution to the molten selenium. Stir at room temperature for 20 min. Then add 10 mL of nickel sulfate solution with pH 0 (of which the mass of nickel sulfate is 0.01 mol) dropwise to the potassium hydroxide solution of selenium. The resulting precipitate is aged for 5 h. The synthesized sample is washed 5 times with deionized water. After solid-liquid separation, the sample is placed in a drying oven and dried at 100℃ for 8 h. The hydrophobic nickel selenide adsorbent is obtained by passing it through a 100-mesh sieve. The hydrophobicity of the prepared nickel selenide is tested using a water contact angle tester (OCA20, Germany). The water contact angle of nickel selenide is measured to be 140°, which belongs to superhydrophobic materials.
[0051] (2) Weigh 100 mg of adsorbent and place it in a cylindrical quartz glass fixed-bed reactor. Elemental mercury is generated through a mercury permeation tube, using nitrogen gas at a flow rate of 1 L / min as the carrier gas. The initial mercury concentration is 100 ± 1 μg / m³. 3 The reaction temperature was 150℃. The concentration of elemental mercury at the inlet and outlet of the reactor was monitored using a VM3000 mercury analyzer. Under N2 and N2+20%H2O conditions, the mercury adsorption capacity of hydrophobic nickel selenide was 20.5 mg / g and 21.7 mg / g, respectively.
[0052] Example 4
[0053] 1 mg of nickel selenide catalyst (the preparation of nickel selenide catalyst is the same as the preparation of nickel selenide adsorbent in Example 3) was weighed and uniformly loaded onto conductive carbon paper. It was placed on the cathode side of an H-type electrolytic cell with an applied voltage of -0.8 V. The electrolyte was a saturated potassium bicarbonate solution, and CO2 gas was introduced at a flow rate of 20 ml / min. The Faradaic efficiency of ethylene production in the reactor was detected by gas chromatography. The measured Faradaic efficiency of hydrophobic nickel selenide for ethylene production was 44%, and the Faradaic efficiency of hydrogen production due to H2O reduction was 24%.
[0054] Example 5
[0055] The only difference between this example and Example 1 is that the molar mass of sulfur powder was changed to 0.1 mol, while all other conditions remained the same. Under pure N2 and N2 + 20% H2O atmospheres, the removal rates of As2O3 after 3 hours were 100% and 75%, respectively. In this comparative example, compared to Example 1, the cadmium sulfide adsorbent prepared by reducing the amount of sulfur powder to half showed a 75% removal rate of As2O3 under an N2 + 20% H2O atmosphere, indicating that the prepared cadmium sulfide adsorbent had low hydrophobicity.
[0056] Example 6
[0057] The only difference between this example and Example 1 is that the molar mass of sulfur powder is changed to 0.03 mol, while the other conditions remain the same. Under pure N2 and N2 + 20% H2O atmospheres, the removal rates of As2O3 after 3 hours were 100% and 55%, respectively.
[0058] Comparative Example 1
[0059] The only difference between this comparative example and Example 1 is that hydrochloric acid solution was not added to adjust the pH during the preparation of the cadmium sulfide adsorbent; all other conditions were the same. Under pure N2 and N2 + 20% H2O atmospheres, the removal rates of As2O3 were 100% and 92% after 3 hours, respectively. In this comparative example, without adding hydrochloric acid to adjust the system pH, the removal rate of As2O3 decreased when the atmosphere contained 20% H2O, indicating that the prepared cadmium sulfide adsorbent had low hydrophobicity.
[0060] Comparative Example 2
[0061] The only difference between this comparative example and Example 2 is that the sulfur powder is not subjected to heating and melting treatment; all other conditions are the same. Simulated flue gas N2, N2 + 5% H2O, N2 + 10% H2O, and N2 + 20% H2O were added respectively, and Hg was measured within 2 hours. 0 The adsorption efficiencies were 100%, 95%, 85%, and 70%, respectively. This comparative example illustrates that when the sulfur powder used is not in a molten state, the adsorption performance of the prepared cobalt sulfide adsorbent decreases significantly in a water-containing atmosphere.
[0062] Comparative Example 3
[0063] The only difference between this comparative example and Example 3 is that the selenium powder was not subjected to heating and melting; instead, it was dissolved after being added to potassium hydroxide solution and then heated to 80°C and stirred for 24 hours. All other conditions remained the same. The concentration of elemental mercury at the reactor inlet and outlet was monitored using a VM3000 mercury analyzer. Under N2 and N2 + 20% H2O conditions, the mercury adsorption capacity of nickel selenide was 20.5 mg / g and 9.8 mg / g, respectively. This comparative example demonstrates that when the selenium powder used is not in a molten state, the adsorption performance of the prepared nickel selenide adsorbent significantly decreases in a water-containing atmosphere.
[0064] Comparative Example 4
[0065] The only difference between this comparative example and Example 3 is that the molar mass of selenium powder was changed to 0.0063 mol, while all other conditions remained the same. 1 mg of nickel selenide catalyst was weighed and uniformly loaded onto conductive carbon paper, placed on the cathode side of an H-type electrolytic cell, and an external voltage of -0.8 V was applied. The electrolyte was a saturated potassium bicarbonate solution, and CO2 gas was introduced at a flow rate of 20 ml / min. The Faradaic efficiency of ethylene production in the reactor was detected by gas chromatography. The measured Faradaic efficiency of nickel selenide for ethylene production was 15%, and the Faradaic efficiency of H2O reduction for hydrogen production was 36%. This comparative example illustrates that when the amount of chalcogenide used is not excessive, the catalytic selectivity of the prepared chalcogenide decreases.
Claims
1. A method for synthesizing a superhydrophobic unsaturated transition metal chalcogenide, characterized in that: Chalcogenide powder is heated to above the melting temperature to form molten chalcogenide. The heating process achieves ring opening of elemental sulfur and / or bond breaking of elemental selenium. The molten chalcogenide is mixed with a reducing agent to undergo a disproportionation reaction to form sulfur chains and / or selenium chains in negative valence states. Then, a strongly acidic solution containing transition metal cations is added for aging to obtain the final product. The molar ratio of the chalcogenide powder to the transition metal cation in the solution containing transition metal cations is 2~20:1; the pH of the strongly acidic solution containing transition metal cations is 0~2; The superhydrophobic unsaturated transition metal chalcogenide compounds contain chalcogen elements that do not exist entirely in their lowest valence form and have a uniform pore structure and surface defect sites. The chalcogenides include elemental sulfur and / or elemental selenium.
2. The method for synthesizing a superhydrophobic unsaturated transition metal chalcogenide according to claim 1, characterized in that: The transition metal cation is at least one of copper, zinc, cadmium, cobalt, iron, molybdenum, and nickel.
3. The method for synthesizing a superhydrophobic unsaturated transition metal chalcogenide according to claim 1, characterized in that: The reducing agent is at least one of sodium hydroxide, sodium borohydride, sodium thiosulfate, potassium hydroxide, and potassium borohydride.
4. The method for synthesizing a superhydrophobic unsaturated transition metal chalcogenide according to claim 1, characterized in that: The amount of reducing agent added is more than 1.5 times the mass of the chalcogenide powder.
5. A method for synthesizing a superhydrophobic unsaturated transition metal chalcogenide according to claim 1 or 3, characterized in that: The conditions for the disproportionation reaction are: a temperature of 20~220°C. o C, time is 10~120 min.
6. The method for synthesizing a superhydrophobic unsaturated transition metal chalcogenide according to any one of claims 1 to 4, characterized in that: The aging process is carried out at room temperature and pressure for 2 to 24 hours.
7. A superhydrophobic unsaturated transition metal chalcogenide, characterized in that: It is obtained by the synthesis method described in any one of claims 1 to 6.
8. The superhydrophobic unsaturated transition metal chalcogenide according to claim 7, characterized in that: In the superhydrophobic unsaturated transition metal chalcogenides, the chalcogen elements do not exist entirely in their lowest valence form.
9. The application of the superhydrophobic unsaturated transition metal chalcogenide according to claim 7 or 8, characterized in that: It is used as an adsorbent for heavy metal elements and / or heavy metal oxides.
10. The application of the superhydrophobic unsaturated transition metal chalcogenide according to claim 7 or 8, characterized in that: It is used as a catalyst for the electrocatalytic reduction of oxidizing gases.
Citation Information
Patent Citations
Supported active chalcogenide compound as well as preparation method and application thereof
CN114700027A
Method for enhancing mercury removal performance of metal sulfide
CN115888625A